Meta-Analysis the Effect of Constraint-Induced Movement Therapy on Hands Functional Ability and Occupational Performance in Children with Cerebral Palsy - Mutiana Agustin Sholikah; Agus Kristiyanto; Hanung Prasetya (Journal of Epidemiology and Public Health, 2021)
Background: Children with cerebral palsy generally experience hand functional disorders which then affect the child's occupational performance. Hand functional ability is the ability to use the hand in doing activities. To be able to perform occupational performance, good hand functional abilities are needed. To achieve this, interventions are needed, one of which is constraint-induced movement therapy (CIMT) which is hypothesized to be able to improve hand functional ability and occupational per-formance. The purpose of this study was to determine the effect of CIMT on the hands functional ability and the occupation performance of children with cerebral palsy.Subjects and Method: This study used a systematic review design and meta-analysis using the PRISMA flow chart guidelines. The process of searching for articles was carried out between 2005-2020 using databases from PubMed, Science Direct, AJOT, Springer Link, and Google Scholar. Based on the database, there were 20 articles that met the inclusion criteria. This study involved 669 subjects of hand functional ability and 440 subjects of occupational performance. The analysis was performed using the RevMan 5.3 software. Results: A total of 20 articles conducted a meta-analysis review. A total of 18 articles conducted a meta-analysis showing that giving CIMT to children with cerebral palsy was significantly able to improve hands functional ability of children with cerebral palsy (SMD = 0.40; 95% CI 0.09 to 0.71; p = 0.01). A total of 11 articles conducted a meta-analysis showing that giving CIMT to children with cerebral palsy was able to improve occupational performance abilities but it was not statistically significant (SMD = 0.18; 95% CI 0.17 to 0.52; p = 0.32).Conclusion: CIMT can improve hand functional abilities and occupational performance of children with cerebral palsy.